The accessibility of airline websites to the handicapped - Ulaş, Halil Göker. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Website accessibility is very important for disabled people to use the Internet. In the light of this matter, the objective of this thesis is to measure the accessibility performances of airline website online ticketing flows for handicapped people. For this purpose, automated accessibility testing was performed for 27 airline websites with automated accessibility checker called Achecker. The tested ticketing flows of websites consisted of homepage, availability page, availability summary page, extra services page, profile page and payment page. According to the automated test results and the specifications of the airlines, statistical analyses were performed in order to see if any of the specifications has a relation with the accessibility performance of an airline. Analyses results show that having a flight to the United States and revenue have significant correlation with the accessibility performance of an airline. Two other specifications which are the profit and type of codebase used for testing also appeared to be significant to some extent despite being less significant than the former two specifications. Thus, it can be concluded that taking appropriate preventive legal measures seem to be a way for airline websites to comply more with accessibility standards. Like the United States, other countries who want to provide more accessible airline websites for disabled people may enact the relevant laws in order to force airlines to conform the accessibility standards.
Keywords: Computers and people with disabilities.; Accessible Web sites for people with disabilities.; Internet users.